2014
DOI: 10.1016/j.devcel.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Function of Cell Shape and Size during Mitosis

Abstract: Dividing cells almost always adopt a spherical shape. This is true of most eukaryotic cells lacking a rigid cell wall and is observed in tissue culture and single-celled organisms, as well as in cells dividing inside tissues. While the mechanisms underlying this shape change are now well described, the functional importance of the spherical mitotic cell for the success of cell division has been thus far scarcely addressed. Here we discuss how mitotic rounding contributes to spindle assembly and positioning, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
187
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(197 citation statements)
references
References 133 publications
9
187
1
Order By: Relevance
“…Studies of multicellular spheroids indicate that the mechanical pressure of the tissue environment can impair cell proliferation (33,34). Moreover, it has been predicted that cells in stiffer or more densely packed tissue environments, such as of an overgrown tumor, would require a more robust cell cortex and mitotic rounding response (9,35). Indeed, although strategies for chemical perturbation of cell division have been pursued for decades (36), the advent of mechanical approaches opens the door to studies of physical perturbation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of multicellular spheroids indicate that the mechanical pressure of the tissue environment can impair cell proliferation (33,34). Moreover, it has been predicted that cells in stiffer or more densely packed tissue environments, such as of an overgrown tumor, would require a more robust cell cortex and mitotic rounding response (9,35). Indeed, although strategies for chemical perturbation of cell division have been pursued for decades (36), the advent of mechanical approaches opens the door to studies of physical perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…In mitosis, cells generate actomyosindependent (1) intracellular pressure to round up and optimize geometry for proper function of the mitotic spindle, the machinery that organizes and segregates chromosomes (2,9,10,22). Restricting cell rounding height below 5-8 μm with microfabricated PDMS chambers perturbs mitotic progression in several cell types (2, 10), but the forces that cells can withstand remain unquantified.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…2 In addition, nuclear volume is expected to increase through the cell cycle leading up to division. We looked at the phase of the top fits (all those included in Tables S1 and S4) that had periods according with the cell cycle (15-22 hours) and found that the eccentricity had an average phase of 0.6645 rad, meaning it peaked 1.5 hours after serum was returned to the cells (and every ' 17 hours after that).…”
Section: Nuclear Shape Changes Over Timementioning
confidence: 99%
“…Abscission eventually resolves the bridge, thereby generating two distinct cells. Therefore, the dividing cell is subjected to various forces that are exerted through its own cytoskeleton (reviewed by Cadart et al, 2014;Kunda and Baum, 2009;Lancaster and Baum, 2014). In cultures of isolated cells, cells are round and exhibit a stiff actomyosin cortex during prometaphase, but upon entry into cytokinesis, cortical tensions become asymmetric -tension at the poles is relaxed, whereas the equator undergoes contraction.…”
Section: Introductionmentioning
confidence: 99%